POLISH-BULGARIAN TRANSLATION OF COURT TEXTS - MAZURKIEWICZ-SUŁKOWSKA, Julia (Comparative Legilinguistics, 2010)
As we know, translation of legal texts requires maximum fidelity and does not allow arbitrary interpretation. This kind of translation is relatively easy as long as the systems of both languages did not show major differences in the gramaticalization of individual contents. In the case of the Bulgarian-Polish translations the biggest problems relate to the differences between the temporal systems of those languages, and differences in the expression of imperceptive modality. The article is devoted to this particular issues.